Heritable pulmonary hypertension: from bench to bedside. (6th September 2017) - Girerd, Barbara; Weatherald, Jason; Montani, David; Humbert, Marc
Mutations in the BMPR2 gene, and more rarely in ACVRL1, endoglin, caveolin-1, KCNK3 and TBX4 genes predispose to heritable pulmonary arterial hypertension, an autosomal dominant disease with incomplete penetrance. Bi-allelic mutations in the EIF2AK4 gene predispose to heritable pulmonary veno-occlusive disease/pulmonary capillary haemangiomatosis, an autosomal recessive disease with an unknown penetrance. In France, the national pulmonary hypertension referral centre offers genetic counselling and testing to adults and children. Predictive testing is also proposed to adult relatives at risk of carrying a predisposing mutation. In that context, we offer all asymptomatic BMPR2 mutation carriers a programme to detect pulmonary arterial hypertension at an early phase, as recommended by the 2015 European Society Society of Cardiology/European Respiratory Society pulmonary hypertension guidelines. Finally, pre-implantation genetic diagnosis has been conducted on five embryos from two couples in which the fathers were carriers of a pathogenic BMPR2 mutation. Genetic counselling and testing available in France for patients at risk of PAH and PVOD/PCH http://ow.ly/m0MA30dBnkF